ANALYSIS OF THE GENOMIC ALIGNMENT OF MUTANT SEQUENCES OF P53 GENE - Alves dos Santos Neto, Antonio; Vaz Fluminhan, Thomas; Fluminhan, Antonio (Journal of Interdisciplinary Debates, 2025)
Bioinformatics tools available on the web were employed to analyze nucleotide sequences in p53 gene mutations from patients with skin carcinoma deposited in genomic banks in the United States and Europe. The feasibility of the proposed approach and the identification of common characteristics among the evaluated mutants were demonstrated. The gene regions most sensitive to changes in nucleotides, which may be related to the origin of the pathology, were identified. Mutations occurring in the p53 gene, which are derived from genetic sequences deposited at the NCBI Institute, are predominantly located in very restricted gene regions, which were identified between positions 23562 and 24735. Mutant sequences deposited at the EBI Institute have shown that the most frequent mutations occurr between positions 19844 and 21786 of the p53 gene. The occurrence of transitions (purine-purine and pyrimidine-pyrimidine) was predominant over the occurrence of transversions in mutants for the p53 gene. The present research demonstrated the multidisciplinary nature of these activities, increasing the relevance and productivity of bioinformatics analyses.